Physical activity, television viewing time, and retinal vascular caliber - Anuradha, S.; Dunstan, D.; Healy, Genevieve; Shaw, J.; Zimmet, P.; Wong, T.; Owen, N. (2011)
Purpose: To examine the associations of physical activity and television (TV) viewing time with retinal vascular caliber in Australian adults. Methods: A total of 2024 adults aged 25 yr or older without known diabetes in the Australian Diabetes, Obesity, and Lifestyle Study (AusDiab, 1999-2000), a population-based cross-sectional study, were evaluated. Retinal vascular calibers (both arteriolar and venular calibers) were measured from digital retinal photographs using a computer-assisted method and were summarized into central retinal artery and vein equivalents. Self-reported physical activity time and TV viewing time were obtained using interviewer-administered questionnaires. Results: For physical activity, no statistically significant multivariate relationships emerged for men or for women. After adjusting for confounders (age, sex, education, cigarette smoking, diet quality, waist circumference, systolic blood pressure, plasma glucose levels, serum fibrinogen, serum triglyceride, and physical activity time), men who watched TV for at least 2 h•d had a venular caliber that was 4.71 µm (95% confidence interval = 1.37-8.04 µm, P = 0.006) wider compared with those watching <2 h•d of TV. No significant association with venular caliber was noted in women. Conclusions: These findings provide the first evidence of an association between TV viewing time (a common, leisure time sedentary behavior) and retinal microcirculation. Further research is needed to examine these associations in different populations and by using more comprehensive physical activity and sedentary behavior measures. © 2011 by the American College of Sports Medicine.